1970
DOI: 10.1007/bf01868016
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an electrogenic ion transport pump in cells of higher plants

Abstract: Cyanide (CN) and dinitrophenol (DNP) rapidly depolarize the cells of oat coleoptiles (Avena sativa L., cultivar Victory) and of pea epicotyls (Pisum sativum L., cultivar Alaska); the effect is reversible. This indicates that electrogenesis is metabolic in origin, and, since active transport is blocked in the presence of CN and DNP, perhaps caused by interference with ATP synthesis, that development of cell potential may be associated with active ion transport. Additional evidence for an electrogenic pump is as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1
1

Year Published

1970
1970
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(56 citation statements)
references
References 23 publications
(31 reference statements)
2
52
1
1
Order By: Relevance
“…This equation should hold for ions passively distributed or for cases in which the ion pumps are neutral. However, there is evidence with seedling tissues that a significant portion of the cell electropotential arises from a metabolically driven electrogenic pump (7,10). In this circumstance the equation would not be expected to fit experimental data on tissue having such transport.…”
Section: Resultsmentioning
confidence: 98%
“…This equation should hold for ions passively distributed or for cases in which the ion pumps are neutral. However, there is evidence with seedling tissues that a significant portion of the cell electropotential arises from a metabolically driven electrogenic pump (7,10). In this circumstance the equation would not be expected to fit experimental data on tissue having such transport.…”
Section: Resultsmentioning
confidence: 98%
“…As illustrated for washed tissue, the PD recovers as the uncoupler is washed out. We will refer to that portion of the PD which is reversibly collapsed by uncoupling as the electrogenic PD; the base potential is the diffusion potential (3,4). Figure 2 shows a slight, nonsignificant increase in diffusion potential during the course of washing.…”
Section: Methodsmentioning
confidence: 99%
“…In other work, Higinbotham and associates have shown that a portion of the measured potential difference across the cytoplasmic layer of higher plant cells is electrogenic (4). Inhibitors or uncouplers of respiration collapse a significant portion of the cell potential, and this is attributed to failure of the energy supply for a metabolically driven ion or proton pump.…”
mentioning
confidence: 99%
“…Higinbotham et al, 1970). In this article we describe for the first time measurements of electric potential difference (p.d.)…”
Section: mentioning
confidence: 99%